Head and face anthropometric study for respirators in the multi-ethnic Asian population of Malaysia - Lim, Yin Cheng; Abdul Shakor, Ameerah Su'ad; Mohamad, Nadia; Pahrol, Muhammad Alfatih; Ismail, Rohaida; Chong, Zhuo Lin; Abdul Mutalip, Mohd Hatta; Omar, Mohd Azahadi; Danaee, Mahmoud; Wan, Guo Tung; Shaharudin, Rafiza (Frontiers in Public Health, 2022)
Background Existing anthropometric studies for respirator designs are based on the head and facial dimensions of Americans and Chinese nationals, with no studies for multi-ethnic countries like Malaysia. This study aimed to create head and facial morphological database for Malaysia, specifically to identify morphological differences between genders, ethnicities, and birthplaces, as well as predictors of the dimensions. Design A cross-sectional study. Setting Malaysia. Participants A nation-wide cross-sectional study using a complex survey design with two stage-stratified random sampling was conducted among 3,324 participants, aged 18 years and above who were also participants of the National Health and Morbidity Survey 2020. Primary and secondary outcomes The study collected data on sociodemographic, measurement of Body Mass Index (BMI) and 10 head and facial dimensions (3 dimensions were measured using direct measurement, and 7 others using Digimizer software for 2-dimension images). Linear regression was performed to determine the association between gender, ethnicity, birthplace, age and BMI and the dimensions. Results There were significant differences in all the dimensions between sex, birthplace and ethnicity (p < 0.005). Further analysis using linear regression showed sex, ethnicity, birthplace, age and BMI were significant predictors of the dimensions. In comparison to studies from the United States and China, our study population had a wider interpupillary distance and nose breadth for both male and female participants, but smaller bigonial breadth and smaller minimal frontal breadth. Conclusion These findings could assist in the design and sizing of respirators that will fit Malaysians and possibly other Southeast Asian population.